Impact of Soybean Nodulation Phenotypes and Nitrogen Fertilizer Levels on the Rhizosphere Bacterial Community - Wang, Hao; Gu, Chuntao; Liu, Xiaofeng; Yang, Chunwei; Li, Wenbin; Wang, Shaodong (Frontiers in Microbiology, 2020)
The effects of nodulation properties of legumes on the rhizosphere bacterial community are still not clear. To determine the effects of nodulation phenotypes on bacterial communities in the rhizosphere of soybean plants, we performed high-throughput sequencing of the 16S rRNA gene to estimate the rhizosphere bacterial community of three soybean lines with different nodulation phenotypes grown in soil supplied with different levels of N fertilizer. The results revealed that both the soybean nodulation phenotypes and the N levels affected the rhizosphere bacteria community, but the nodulation phenotypes contributed more than the N-supply. The diversity of bacteria was decreased in the rhizosphere of super-nodulating phenotype. The response of rhizosphere bacterial communities to the soil available nitrogen (AN) concentrations was different than the response with the three nodulation phenotypes of soybean which was more stable in the wild-type (Nod+) soybean samples than that in the mutant samples (Nod– and Nod++). Bradyrhizobium in the rhizosphere was positively correlated with nodule number and negatively correlated to AN in the soil, while Burkholderia and Dyella were positively correlated with nodule biomass and nitrogenase activity. These results demonstrated that the nodulation phenotype of soybean affects the rhizosphere microbiome.